(untitled) - Ketley, Julian M. (Norfolk NR., 2005)
Horizon Scientific Press titles focus on high-level microbiology and molecular biology topics. Written by internationally renowned and highly respected leaders in the field, they comprise of review manuals, practical manuals, and reference texts for research scientists, bioscience professionals and graduate students. The publication of the complete sequence of the C. jejuni genome in 2000 provided new insight into this leading gastrointestinal pathogen and presented scientists with an exciting resource to improve our understanding of the biology of this bacterium. In this book internationally recognized Campylobacter experts critically review the most important aspects of Campylobacter research, providing the first coherent picture of the organism's molecular and cellular biology since the publication of the genome. Most contributions are written from a molecular and genomic perspective and contain speculative models upon which to base future research efforts. Introductory chapters explore the taxonomy, genetic diversity, habitats, and epidemiological analysis of campylobacters. Other chapters review Campylobacter plasmid biology, antimicrobial resistance, stress response, motility, chemotaxis, metabolism and bioenergetics of C. jejuni, and polysaccharide biosynthesis (including lipooligosaccharide, capsule biosynthesis, and protein glycosylation). The final chapters focus more directly on interactions with the host, for example, the mechanisms of host cell invasion, interactions with phagocytes, and the use of microarrays to analyze gene expression in response to infection by C. jejuni. Each chapter is independent and can be read in isolation, but as a whole the book provides an important resource summarizing our current knowledge of Campylobacter molecular and cellular biology.
Keywords: Molecular biology,Periodicals,Molecular biology; Periodicals,Cytology,Periodicals